Cybercriminals impersonating religious institutions and leaders for financial gains: an exploration of popular pentecostal ministries - Tshifhumulo, Rendani; Mudau, Ndidzulafhi (International journal of business ecosystem & strategy, 2025)
The growing number of cybercriminals impersonating religious leaders and institutions for financial gain poses a serious threat to the integrity and economic security of religious groups, notably prominent Pentecostal ministries. This study thoroughly investigates and evaluates this phenomenon, focusing on cybercriminals' tactics, the scope of their actions, and the consequences for targeted religious communities and people. The study applies a complete desktop research technique to analyse hackers' use of religious leaders' identities for financial benefit, focusing on Pentecostal ministries. This strategy includes searching academic databases, reading cybersecurity and religious studies journals, and analysing documented cases. The findings show that cybercriminals are primarily driven by financial gain and use strategies including building phoney social media pages, phishing techniques, and compromising communication lines to impersonate religious groups and scam congregants. This study contributes to developing more effective defences against cyber fraud in religious contexts by evaluating religious institutions' responses and mitigation techniques, as well as law enforcement. This project intends to develop more effective techniques for preventing and combating cyber-fraud against religious bodies through an in-depth examination.